Educational Effectiveness of Type 2 Diabetes Mellitus Patients in Rural Areas in Controlling Blood Glucose: Literature Review - Hasbi, Masna; Kusbaryanto, K; Prasetyo, Mahendro (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Type 2 diabetes mellitus is a chronic disease that has received attention from WHO. Every patient diagnosed with T2DM must undergo routine examination and treatment for the rest of his life. The increasing incidence of diabetes mellitus in rural areas is also a focus for the government. One of the causes of the prevalence of T2DM in rural areas is the low level of knowledge and awareness of diabetic patients about their disease. Education is an important part for people with T2DM to increase their self-awareness. Education is one approach to patients who are reported to be able to improve the body condition of T2DM patients. The purpose of this research is to conduct a case study of literature review about the methods of education for T2DM in rural areas developed by other authors. The author found 12 articles related to educational methods for T2DM patients in rural areas. The educational methods provided are in two broad outlines including direct or indirect (electronic and application). The advantage of the direct education method is that health workers can see the patient's condition, while indirectly they cannot. The advantages of the indirect method are easy and cheaper, and can be done anytime and anywhere.Abstrak: Diabetes mellitus type 2 merupakan satu penyakit kronik yang mendapat perhatian dari WHO. Setiap pasien yang terdiagnosis DMT2 harus melakukan pemeriksaan dan pengobatan secara rutin seumur hidupnya. Angka kejadian diabetes mellitus di pedesaan yang semakin meningkat juga menjadi fokus bagi pemerintah. Salah satu penyebab prevalensi DMT2 di pedesaan adalah rendahnya angka pengetahuan dan kesadaran pasien diabetes akan penyakitnya. Edukasi merupakan salah satu bagian penting bagi penderita DMT2 untuk meningkatkan kesadaran dirinya. Edukasi merupakan salah satu pendekatan kepada pasien yang dilaporkan dapat membuat kondisi tubuh pasien DMT2 menjadi membaik. Tujuan dari penelitian ini adalah penulis melakukan studi kasus literatur review tentang metode-metode edukasi DMT2 di pedesaan yang dikembangkan oleh penulis lain. Penulis mendapatkan 12 artikel yang terkait tentang metode edukasi bagi pasien DMT2 di pedesaan. Metode edukasi yang diberikan dalam dua garis besar diantaranya secara langsung ataupun secara tidak langsung (elektronik dan aplikasi). Kelebihan metode edukasi secara langsung adalah petugas kesehatan dapat melihat kondisi pasien, sedangkan secara tidak langsung tidak bisa. Kelebihan metode tidak langsung mudah, biaya lebih murah dan bisa kapanpun dan dimanapun.